2019
DOI: 10.1002/jcp.29304
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker expression analysis in different age groups revealed age was a risk factor for breast cancer

Abstract: The relationship between age and breast cancer is ambiguous. Here, we analyzed the differential expression pattern of long noncoding RNAs (lncRNAs) and messenger RNAs (mRNAs) in different age groups to provide an effective association between age and breast cancer risk at the molecular level. We integrated the microarray information from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) data sets. The patients were divided into young ( < 50 years) and old ( ≥ 50 years) age groups and evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Global cancer burden 2017 attributed the variations in BC incident rates to population growth and aging process [32] . Various other studies have also supported the findings that being a complex chronic systemic disease, BC likely to have significant association with age, as disease incidence increases with increased age [33] , [34] , [35] , [36] , [37] . Decreased deaths and DALYs among developed countries were attributed to the adoption of widespread mammographic screening of the disease [15] , [33] .…”
Section: Discussionmentioning
confidence: 66%
“…Global cancer burden 2017 attributed the variations in BC incident rates to population growth and aging process [32] . Various other studies have also supported the findings that being a complex chronic systemic disease, BC likely to have significant association with age, as disease incidence increases with increased age [33] , [34] , [35] , [36] , [37] . Decreased deaths and DALYs among developed countries were attributed to the adoption of widespread mammographic screening of the disease [15] , [33] .…”
Section: Discussionmentioning
confidence: 66%
“…As a major member of the metallothionein family, MT1M is a cysteine-rich metal-binding protein that is induced by in ammation and protects the cell against carcinogens. Emerging evidence has shown that MT1M is related to pancreatic ductal adenocarcinoma [36], breast cancer [37], renal cell carcinoma [38] and colorectal carcinoma [39]. In colorectal cancer, MT1M was a highly expressed isoform in tumor epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…We believe the reason for the inconsistent results was due to different microarray platforms of the 2 datasets, different sample sizes, and heterogeneities between the species and tissues. Consequently, to further identify the potential function of the hub genes in GIOP, GSEA was conducted to search KEGG pathways enriched in the highly expressed samples, as previously reported [ 34 , 35 ]. In our results, the focal adhesion and the ECM receptor interaction pathways notably showed significant enrichment within samples showing high COL1A3 and COL6A3 expression levels.…”
Section: Discussionmentioning
confidence: 99%